2006
DOI: 10.1039/b606900b
|View full text |Cite
|
Sign up to set email alerts
|

Functional dependency of structures of ionic liquids: do substituents govern the selectivity of enzymatic glycerolysis?

Abstract: The concept of regulating the preference of a reversible multi-step reaction by adjusting the substituents of ionic liquids (ILs) has been successfully exemplified with a group of tetraammonium-based ionic liquids as medium for the enzymatic glycerolysis. Simultaneous existence of long chain hydrophobic substituents and hydrophilic ethoxyl or hydroxyl moieties is found, respectively, to be essential for triglycerides (TG) dissolving and equilibrium shifting. The reactions in the ILs with cations consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…4 4 ] than in PF 6 − and BF 4 − based ILs. Xu and co-workers 183,185 utilized the conductorlike screening model for real solvents (COSMS-RS) to derive various parameters (such as misfit, H-bonding and van der Waals interaction energy) to understand the multiple interactions in ILs; the model also provides guidance in designing the structures of cations and anions. 190 The Kragl group 191 found that an IL in the Ammoeng family -Ammoeng 110 ( Fig.…”
Section: Manipulation/design Of Il Structuresmentioning
confidence: 99%
“…4 4 ] than in PF 6 − and BF 4 − based ILs. Xu and co-workers 183,185 utilized the conductorlike screening model for real solvents (COSMS-RS) to derive various parameters (such as misfit, H-bonding and van der Waals interaction energy) to understand the multiple interactions in ILs; the model also provides guidance in designing the structures of cations and anions. 190 The Kragl group 191 found that an IL in the Ammoeng family -Ammoeng 110 ( Fig.…”
Section: Manipulation/design Of Il Structuresmentioning
confidence: 99%
“…The derived interaction items from COSMO-RS calculation can be conversely used for molecular force field analysis to correlate interaction parameters with structural characteristics qualitatively and quantitatively, which is of general instruction value in the design and development of ILs for specific tasks 20,26,27 . Thus, besides presenting the predicted results of flavonoids in ILs and experimental validation of the COSMO-RS prediction, this work gives more attention on the analysis and assortment of interactions resulted from the specific environment of the ILs applied.…”
mentioning
confidence: 99%
“…However, screening a desired structure with required properties for a particular task from a large pool of available ILs represents a big challenge facing chemists and engineers 13,18,19 . To establish an efficient IL-based enzymatic reaction system to product lipophilic derivatives of flavonoids, there exist similar obstacles for the setup of such a reaction system to fulfill the requirement of high productivity and simultaneously being benign for enzyme activity 20 . Solubility estimation approaches could be quite valuable in reducing time and resources required to identify a good solvent screening is needed, because it is impractical to use trial and error methods to find a suitable IL from enormous number of ILs structurally possible for a given function.…”
mentioning
confidence: 99%
“…The relatively lower reaction rates may be attributed to the lower solubility of the triglyceride in the BMI·NTf 2 ionic liquid as already observed in the lipase-catalyzed glycerolysis [25] of triolein. [26] Therefore, it can envisaged that more efficient catalytic systems [27] may be obtained by the use of task-specific ionic liquids such as those containing hydrophobic substituents in the cation that are known to contribute to the increase of triglyceride solubility and consequently can cause an enhancement of the initial reaction rate.…”
Section: Resultsmentioning
confidence: 87%